ATIS - Firsi Juniantha (Saraswati)
ATIS is a dance that reflects the experience that has over been felt by all the creature, every single person on the surface of the earth about cildness, whether it’s a kind of coldness as expression or as effects that subjectively appeared by the coldness it self are, so that it is interesting to be input into parts of the dance. This kind of choreography in group that is performed by seven dancers, including four female dancers and three male dancers. This dancer consists of four main parts with suite concept. Performance art with suite concept which is applied in a choreography, will create a short work of dance art with more than one stories in one dance, which each part of the dance doesn’t relate to the others, but over all it is in one theme. In this ATIS dance the story or the impression that is wanted to be delivered to the audience, is different from one part to the other, but it is talking about the same main theme, that is coldness. Key word: ATIS, Coldness, Suite